Further delineation of Pitt–Hopkins syndrome: phenotypic and genotypic description of 16 novel patients. Issue 11 (26th August 2008) - Zweier, C; Sticht, H; Bijlsma, E K; Clayton-Smith, J; Boonen, S E; Fryer, A; Greally, M T; Hoffmann, L; den Hollander, N S; Jongmans, M; Kant, S G; King, M D; et al.
Abstract : Background: Haploinsufficiency of the gene encoding for transcription factor 4 ( TCF4 ) was recently identified as the underlying cause of Pitt–Hopkins syndrome (PTHS), an underdiagnosed mental-retardation syndrome characterised by a distinct facial gestalt, breathing anomalies and severe mental retardation. Methods: TCF4 mutational analysis was performed in 117 patients with PTHS-like features. Results: In total, 16 novel mutations were identified. All of these proven patients were severely mentally retarded and showed a distinct facial gestalt. In addition, 56% had breathing anomalies, 56% had microcephaly, 38% had seizures and 44% had MRI anomalies. Conclusion: This study provides further evidence of the mutational and clinical spectrum of PTHS and confirms its important role in the differential diagnosis of severe mental retardation.